The The Analysis of Symbolism Related to Ecocriticism Found In Movie “Man” by Steve Cutts - Komang, Ni Komang Trisya Suasti (ID Solutions, 2024)
This comprehensive study endeavors to delve deeply into the intricate relationship between eco-criticism and symbolism within the captivating realm of the illustrated film